Ability of salt marsh plants for TBT remediation in sediments - Carvalho, P. N. (2014)
The capability of Halimione portulacoides, Spartina maritima, and Sarcocornia fruticosa (halophytes very commonly found in salt marshes from Mediterranean areas) for enhancing remediation of tributyltin (TBT) from estuarine sediments was investigated, using different experimental conditions.